Penggunaan Model Pembelajaran Kooperatif Tipe Think Pair Share Untuk Meningkatkan Penguasaan Konsep Elastisitas dan Hukum Hooke Pada Peserta Didik Kelas XI IPA SMA Negeri 6 Ambon - Munthalib, Christabella C.; Huliselan, Estevanus Kristian; Malawau, Seska; Esomar, Katerina (Pattimura University, 2023)
This study aims to improve mastery of the concept of elasticity and Hooke's law in class XI IPA-1 SMA Negeri 6 Ambon with a cooperative learning model of think pair share type. This type of research is descriptive research with one group pretest-posttest design. The students used as samples in this study were 23 people obtained using a random sampling technique. Research data were collected using test instruments in the form of initial tests and final tests. The results showed that 100% of students' initial concept mastery ability was in the failing category, with an average score of 8,43. After applying the learning model, the average final test score is 91,48 with very good qualifications. This condition causes the average result of the N-Gain test to be an indicator of increasing students' concept mastery to 0,91 in the high category. Thus, using the cooperative learning model type think pair share can improve the mastery of elasticity and Hooke's law in class XI IPA SMAN 6 Ambon students.